Oprah Winfrey : a biography - Garson, Helen S. (Jaico, Mumbai, 2012)
Oprah's life is a bonafide rags-to-riches story that is much more compelling because of her empathy, sense of humor, and ability to communicate and connect with people. Beyond the estimated 30 million American viewers who tune into her television show each week, there are devoted fans in 140 countries where Oprah's show is broadcast. Her life and businesses continue to expand, now encompassing a radio channel, two magazines, and the forthcoming OWN: The Oprah Winfrey Network television channel. This book documents the different aspects of Oprah's life, incorporating the details of her public, private, and philanthropic personas. The seven chapters of Oprah Winfrey: A Biography, Second Edition span the time period from her childhood in rural Mississippi to her present-day status as a global superstar and philanthropist.
Includes bibliography and index.
Keywords: Biography; Television celebrity